Development of a fully nonlinear, coupled numerical model for assessment of floating tidal stream concepts. (15th December 2020) - Brown, S.A.; Ransley, E.J.; Zheng, S.; Xie, N.; Howey, B.; Greaves, D.M.
Abstract: Compared with existing seabed mounted systems, floating tidal concepts offer an increase in viable sites, along with the ability to harvest higher flow speeds near the free surface. However, such systems will be required to survive in high-energy wave-driven environments, and the performance and survivability of such systems is largely unknown. Current industry standards generally use a decoupled numerical approach to assess this problem, but this paper presents the development of a framework for an efficient numerical tool that is capable of predicting the fully nonlinear, coupled behaviour of floating tidal stream systems. Using the open-source CFD libraries of OpenFOAM as a basis, and a previously developed computationally efficient turbine model, the framework has been demonstrated using a generalised system. Verification against alternative codes based on linear potential theory shows good agreement when the floating structure is considered alone in linear waves. Systematic introduction of mooring forces and the turbine model demonstrates that it is necessary to consider all components of a floating tidal concept simultaneously, and that coupling between platform motion and fluid flow can substantially increase the cyclic amplitude of the turbine loading compared with a fixed device. Highlights: A coupled CFD model for assessment of full floating tidal stream systems is presented. A generic system comprised of a cylindrical structure, turbine and mooring is used for demonstration. The model is verified against current industry standards in wave only conditions. Systematic introduction of components shows coupled modelling of the whole device is important. Coupling between platform motion and the flow is observed to increase cyclic loading amplitude.